The Future of Frozen Conflicts: Understanding the Evolution of Russia's Strategy in the Near Abroad and What is Next - ONACIU, Vlad (Studia Universitatis Babeș-Bolyai Historia, 2022)
Frozen conflicts and the near abroad are concepts that have defined Russia's security policy since the dissolution of the Soviet Union. Firstly, in this paper, we will try to explain how the Kremlin sees its near abroad and how it defines it as part of its sphere of influence. Consequently, it describes its interventions and its inevitable clash with the West. Secondly, we want to frame frozen conflicts in two periods with defining characteristics. Each was marked by who held power in the Kremlin and Russia's economic and military situation at the time. In the end, we want to reflect on the impact of the war in Ukraine on the future of these two concepts. Obviously, the outcome will obviously influence Moscow's ability to project power in the near future and its use of frozen conflicts to achieve this. Article history: Received: 12.05.2022; Revised: 28.07.2022; Accepted: 28.07.2022; Available online: 15.09.2022 Rezumat: Conflictele înghețate şi străinătatea apropiată sunt două concepte care au definit politica de securitate a Rusiei după dizolvarea Uniunii Sovietice. În primul rând, vom încerca să explicăm cum percepe Kremlinul străinătatea apropiată şi cum o defineşte ca parte din sfera sa de influență. Aceasta a ajuns să descrie intervențiile aici şi inevitabila sa ciocnire cu Occidentul. În al doilea rând, dorim să încadrăm conflictele înghețate în două perioade cu caracteristici specifice. Fiecare a fost marcată de cine a deținut putere la Kremlin, precum şi de situația economică şi militară a Rusiei la momentul respective. La final dorim să reflectăm impactul războiului din Ucraina asupra celor două concept analizate. Este evident că rezultatul va influența abilitatea Moscovei de a-şi proiecta puterea în străinătatea apropiată, precum şi a folosirii conflictelor înghețate în acest scop. Cuvinte cheie: conflicte înghețate, străinătate apropiată, politică de securitate, Ucraina, Rusia